Reversible computation : 10th International Conference, RC 2018, Leicester, UK, September 12-14, 2018, Proceedings /: 10th International Conference, RC 2018, Leicester, UK, September 12-14, 2018, Proceedings. (2018) - Unknown
No abstract available